Instructions for writers - Escobar Triana, Jaime Alberto (Revista Colombiana de Bioética, 2015)
The Revista Colombiana de Bioetica, an expressive tool from the Department of Bioethics at the Universidad El Bosque, is a semester publication arbitrated and addressed to the reader interested in knowing about the extent, transdisciplinary, and complexity of Bioethics. The Journal accepts projects done in Spanish, and in other languages such as French and English.